Effects of long-term oral administration of styrene to mice and rats. - Ponomarkov, Vladimir; Tomatis, Lorenzo (Scandinavian Journal of Work, Environment & Health, 1978)
Styrene monomer dissolved in olive oil was given orally to female O20 mice (1,350 mg/kg), C57 Bl mice (300 mg/kg) and BD IV rats (1,350 mg/kg) on the 17th day of gestation. Their offspring were treated weekly with styrene by stomach tube from the time of weaning throughout their life-span. The weekly doses used were 1,350 mg/kg for O20 mice, 300 mg/kg for C57 Bl mice, and 500 mg/kg for BD IV rats. Following the continuous oral administration of styrene for over 100 weeks, an increased and earlier appearance of lung tumors was observed in O20 mice. A few tumors rarely seen in controls were observed in BD IV styrene-treated rats, and a slightly increased incidence of liver tumors was found in C57 Bl mice. In both cases, however, the total incidence of tumors was not significantly different from that of the controls. The present results provide weak evidence of the carcinogenicity of styrene in one of the two strains of mice tested, when it is given at a high dose level.
Keywords: acute toxicity; administration; carcinogenicity; long-term administration; long-term oral administration; mouse; oral administration; rat; styrene